Open to competition? Competitive density and the growth of young New Zealand ventures - Whittaker, DH; Fath, B; Fiedler, A (SAGE Publications, 2019)
Drawing on 180 survey responses from young, New Zealand-based ventures, we investigate effects of the number of perceived serious competitors on venture growth. We find empirical evidence for an inverse U-shaped relationship between competitive density and young venture growth. We further find that persistent innovation – requiring both initial innovative intent and a recent record of innovation – not only promotes young growth but also moderates the relationship between competitive density and young venture growth. Overall, the study shows that the growth of young ventures committed to persistent innovation is less affected by competitive dynamics compared to non-innovators.